KONSEP PENATAAN KAWASAN SUCI MARGI AGUNG PURA BESAKIH (SUATU KAJIAN LATAR BELAKANG FILOSIFIS) - Bagus Oka, I Gusti (Jurnal Natah; Vol. 2, No. 2 Agustus 2004, 2012)
Besakih temple is the greatest temples in Bali. The main road or margi agung leading to the temple, located in a symmetrical axis with candi bentar or main gate of the Penataran Agung Temple, as an exit gate. This gate is representing the greateness, holiness, and sacredness of this holy area. Residence area which located in left and right side if this margi agung, sometime create some problem because that is, some think could be given result in disgrace of this holy area, especially when the people in this residence establishing a ceremonial event subjected to their forefather. In addition, there are many others problem which can disturb the smoothness and the pleasantness of the traffic toward the temple, caused by combined circulation such as pemedek, tourist, and ceremonial procession itself, which done in margi agung. The result shows that main road of Besakih holy area is a sacred main axis and main orientation for housing around them. The other hand, we need restructuring kiosks all along margi agung. So I suggest that we must keep conservation, holiness, and sacredness of main road of Besakih holy area.
Keywords: main road, main gate, and holy area.